1999
DOI: 10.1074/jbc.274.12.7952
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of β-Amyloid Secretion by FE65, an Amyloid Protein Precursor-binding Protein

Abstract: The principal component of Alzheimer's amyloid plaques, A␤, derives from proteolytic processing of the Alzheimer's amyloid protein precursor (APP). FE65 is a brain-enriched protein that binds to APP. Although several laboratories have characterized the APP-FE65 interaction in vitro, the possible relevance of this interaction to Alzheimer's disease has remained unclear. We demonstrate here that APP and FE65 co-localize in the endoplasmic reticulum/Golgi and possibly in endosomes. Moreover, FE65 increases transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
191
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(206 citation statements)
references
References 45 publications
11
191
4
Order By: Relevance
“…Experimental evidence did not help to definitively address this point. Indeed, there are reports indicating that Ab production is increased by Fe65 overexpression (33) and reduced by Fe65 knockdown (34), whereas other studies reported that FE65 increased sAPPa and decreased Ab production (10). Apparently, the results obtained in animal models are similarly conflicting: APP knock-in mice carrying the Y682G mutation, which abolishes the binding of Fe65, showed decreased levels of Ab and a massive increase in soluble APPa (35).…”
Section: Fe65 As a Regulator Of App Proteolytic Processingmentioning
confidence: 99%
“…Experimental evidence did not help to definitively address this point. Indeed, there are reports indicating that Ab production is increased by Fe65 overexpression (33) and reduced by Fe65 knockdown (34), whereas other studies reported that FE65 increased sAPPa and decreased Ab production (10). Apparently, the results obtained in animal models are similarly conflicting: APP knock-in mice carrying the Y682G mutation, which abolishes the binding of Fe65, showed decreased levels of Ab and a massive increase in soluble APPa (35).…”
Section: Fe65 As a Regulator Of App Proteolytic Processingmentioning
confidence: 99%
“…The highly conserved phosphotyrosine binding (PTB) domains in all three Mint proteins have been shown previously to bind directly to the YENPXY motif of APP (Borg et al, 1996(Borg et al, , 1998Zhang et al, 1997;Sastre et al, 1998;Tanahashi and Tabira, 1999;Tomita et al, 1999;Ho et al, 2002;Araki et al, 2003). Other PTB domain containing proteins have similarly been shown to bind APP, including the Fe65 (Sabo et al, 1999) family, Dab2 (Howell et al, 1999), JIP1b (King et al, 2004), and ARH (Noviello et al, 2003). These proteins can each impact APP traffic and processing in a variety of ways, although where they act is unknown (Selkoe, 1998;Sabo et al, 1999;Lau et al, 2000;King et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other PTB domain containing proteins have similarly been shown to bind APP, including the Fe65 (Sabo et al, 1999) family, Dab2 (Howell et al, 1999), JIP1b (King et al, 2004), and ARH (Noviello et al, 2003). These proteins can each impact APP traffic and processing in a variety of ways, although where they act is unknown (Selkoe, 1998;Sabo et al, 1999;Lau et al, 2000;King et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins, which all bind to the intracellular C-terminal part of APP, are Fe65 (Guenette et al 1999;Sabo et al 1999), X11 Sastre et al 1998), mammalian disabled, mDab1 (Trommsdorff et al 1998;Homayouni et al 1999), JNKinteracting protein-1, JIP-1b (Matsuda et al 2001), a major brain GTP-binding protein, G o (Nishimoto et al 1993), a microtubule-interacting protein, PAT-1 (Zheng et al 1998) and APP-BP1 (Chow et al 1996). Fe65, X11, mDab1 and JIP-1b are adaptor proteins that have a phosphotyrosinebinding domain responsible for the interaction with the YENPTY motif in the cytoplasmic tail of APP.…”
mentioning
confidence: 99%